2020
DOI: 10.1016/j.watres.2019.115238
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 3-year outdoor operation of a flat-panel membrane photobioreactor to treat effluent from an anaerobic membrane bioreactor

Abstract: A membrane photobioreactor (MPBR) plant was operated continuously for 3 years to evaluate the separate effects of different factors, including: biomass and hydraulic retention times (BRT, HRT), light path (Lp), nitrification rate (NOxR), nutrient loading rates (NLR, PLR) and others. The overall effect of all these parameters, which influence MPBR performance had not previously been assessed. The multivariate projection approach chosen for this study provided a good description of the collected data and facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…It has been suggested that the thickness of FPPBR should be limited to 5 cm to allow efficient light penetration (Adessi & De Philippis, 2014; Basak et al, 2014; Marsullo et al, 2015). However, a 10 cm‐thick, 10 L FPPBR was used for laboratory growth of PNSB (Lu et al, 2020) and FPPBR of 10 cm thickness (230 L volume) and 25 cm thickness (550 L volume) were used for long‐term outdoor operation (Gonzalez‐Camejo et al, 2020). On the other hand, a thin‐film FPPBR, with a cross‐section of 61.2 m 2 and a thickness of 3.26 cm, allowed scale‐up to 2000 L for mass cultivation of microalgae (Yan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the thickness of FPPBR should be limited to 5 cm to allow efficient light penetration (Adessi & De Philippis, 2014; Basak et al, 2014; Marsullo et al, 2015). However, a 10 cm‐thick, 10 L FPPBR was used for laboratory growth of PNSB (Lu et al, 2020) and FPPBR of 10 cm thickness (230 L volume) and 25 cm thickness (550 L volume) were used for long‐term outdoor operation (Gonzalez‐Camejo et al, 2020). On the other hand, a thin‐film FPPBR, with a cross‐section of 61.2 m 2 and a thickness of 3.26 cm, allowed scale‐up to 2000 L for mass cultivation of microalgae (Yan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, after day 10, the ambient conditions changed (temperature increased round 5ºC and solar PAR suffered a significant reduction) and probably favoured nitrifying bacteria growth. 16 In addition, the culture was expected to be under ammonium-limited conditions, since NH 4 -N concentration was under 10 mg N•L -1 . 55 This situation made the nitrification rate (NOxR) (which measures the nitrate and nitrite produced through nitrification and is used as an indicator of nitrifying bacteria activity 16,56 increase during Period A to a maximum of 9.3 mg N•L -1 •d -1 (Fig.…”
Section: Effect Of Outdoor Conditions On the Eom Contentmentioning
confidence: 99%
“…In fact, light and competition with nitrifying bacteria have been reported to be key factors in microalgae cultivation systems. 63,16,38,64 Hence, the higher normalised EOM in the culture might not have been the main factor in the lower microalgae cultivation performance observed by the end of both Periods A and B. It will thus be necessary to monitor the system for longer operating periods and to relate all the possible factors which influence nutrient recovery and biomass productivity to properly assess the weight of each individual factor on MPBR performance.…”
Section: Continuous Operation Of Microalgae Cultivationmentioning
confidence: 99%
See 2 more Smart Citations